The Association of a Frailty Index and Incident Delirium in Older Hospitalized Patients: An Observational Cohort Study - Sillner AY (Dove Medical Press, 2020)
Andrea Yevchak Sillner,1,2 Robert Owens McConeghy,1 Caroline Madrigal,1 Deborah J Culley,3 Rakesh C Arora,4,5 James L Rudolph1,6 1Center of Innovation in Long Term Services and Supports, Providence Veterans Affairs Medical Center, Providence, RI, USA; 2College of Nursing, The Pennsylvania State University, University Park, PA, USA; 3Department of Anesthesiology, Perioperative and Pain Medicine, Brigham and Women’s Hospital, Harvard Medical School, Boston, MA, USA; 4Max Rady College of Medicine, Department of Surgery, University of Manitoba, Manitoba, ON, Canada; 5Cardiac Sciences Program, St. Boniface Hospital, Winnipeg, ON, Canada; 6Warren Alpert Medical School and School of Public Health, Brown University, Providence, RI, USACorrespondence: Andrea Yevchak Sillner Email amy139@psu.eduIntroduction/Background: Frailty identifies patients that have vulnerability to stress. Acute illness and hospitalization are stressors that may result in delirium and further accelerate the negative consequences of frailty.Purpose: The purpose of this study was to determine whether frailty, identified at hospital admission and as measured by a frailty index, is associated with incident delirium.Methods: A retrospective, observational, cohort study was done at a Veterans hospital between January 2013 and March 2014. English-speaking patients over 55 years were eligible. Exclusion criteria included inability to complete baseline assessments due to pre-existing cognitive impairment, emergent surgery; and/or admission from a nursing home, pre-existing delirium, and those with psychiatric disease or substance use disorder.Main Outcomes and Measures: Frailty index (FI) variables included cognitive screening, physical function and comorbidities. The FI was calculated as a proportion of possible deficits (range 0 to 1; higher scores indicate increased frailty). Incident delirium was measured daily by an expert clinician interview.Results: A total of 247 patients were admitted and 218 met inclusion/exclusion criteria, with a mean age of 71.54 years (SD = 9.53 years) and were predominantly white (92.7%) and male (91.7%). Participants were grouped using FI ranges as non-frail (FI < 0.25, n=56 (26%)), pre-frail (FI =0.25– 0.35, n=86 (39%)), and frail (FI > 0.35, n=76 (35%)). Pre-frailty and frailty were associated with incident delirium (non-frail: 3.6% vs pre-frail: 20.9% vs frail: 29.3%, p=0.001) and total delirium days (mean day =non-frail 0.04 vs pre-frail 0.35 vs frail 0.57, p=0.003). After adjustment for sociodemographic factors, pre-frail (adjusted OR=5.64, 95% CI: 1.23, 25.99) and frail status (adjusted OR=6.80, 95% CI: 1.38, 33.45) were independently associated with delirium.Conclusion: This study demonstrates that a frailty index is independently associated with incident delirium and suggests that admission assessments for frailty may identify patients at high risk of developing delirium.Keywords: delirium, frailty, frailty index, Veterans, hospital